Association between use of nicotine replacement therapy for harm reduction and smoking cessation: a prospective study of English smokers. Issue 2 (1st December 2011) - Beard, Emma; McNeill, Ann; Aveyard, Paul; Fidler, Jenny; Michie, Susan; West, Robert
Abstract : Aims: It is important to know how far smokers' attempts at using nicotine replacement therapy (NRT) for smoking 'harm reduction' (reducing harm from continued smoking) promote or undermine cessation. To contribute to that goal, this study aimed to assess whether smokers' reports of smoking reduction (SR) and the use of NRT for SR and temporary abstinence (TA) predicted subsequent attempts to quit smoking and smoking status in a population sample. It also examined whether use of NRT for SR or TA was associated with reduced cigarette consumption compared with SR without NRT and non-use of NRT for TA. Method: Data were collected from 15 539 smokers involved in the Smoking Toolkit Study, a series of monthly household surveys of adults aged 16+; of whom 23% (n=3149) completed a 6-month follow-up questionnaire. At baseline, participants were asked whether they were currently using NRT for SR or TA. They were also asked for demographic information and daily cigarette consumption. At 6-month follow-up, data on attempts to quit smoking and smoking status were collected. Results: NRT use for SR and TA prospectively predicted attempts to quit smoking (OR 1.61, 95% CI 1.30 to 2.01 and OR 1.94, 95% CI 1.56 to 2.38 for SR and TA respectively) and abstinence (OR 1.51, 95% CI 1.06 to 2.16 and OR 2.09, 95% CI 1.51 to 3.34 for SR and TA respectively) at 6-months follow-up. Use of NRT for SR or TA was associated with a small reduction in cigarette consumption (two cigarettes per day) compared with SR without NRT or non-use of NRT for TA. Conclusions: The use of NRT for SR or TA appears to be positively associated with subsequent attempts to quit smoking and abstinence among smokers in England, despite very little apparent effect on daily cigarette consumption. With replication, these findings support the potential benefit of using NRT for harm reduction but primarily as a means of promoting cessation.